Kontribusi Supervisi Pengajaran, Sarana Prasarana Dan Komitmen Terhadap Kinerja Guru Di SMA Negeri Kabupaten Grobogan - Ambarwati, Yuni Dwi, Prof. Dr. Sutama,M.Pd, Dr. Sofyan Anif, M. Si (2017)
This study aims to: (1) analyze and examine the contribution of supervision of teaching, infrastructure and commitment of teachers on teacher performance in SMA Grobogan. (2) analyze and examine the contribution of teachers' commitment in SMA Grobogan (3) analyze and examine the contribution of infrastructure in SMA Grobogan. (4) analyze and examine the contribution of teaching supervision in SMA Grobogan. This research uses quantitative methods, this study was conducted in SMA Negeri Pulokulon Grobogan. The results of the study, (1) There is a positive contribution jointly or simultaneously between supervision of teaching, infrastructure and commitment of teachers on teacher performance in SMA Grobogan. The independent variable supervision of teaching, infrastructure and teachers' commitment to jointly affect teacher performance dependent variable 77.7% and the remaining 22.3% is influenced by other variables not included in this study. (2) The positive contribution to the performance of teachers teaching supervision in SMA Grobogan with large donations effectively supervise the performance of teachers teaching in SMA Grobogan of 23.0%, while the relative contribution of 29.6%. (3) There is a positive contribution of infrastructure to the performance of teachers in SMA Grobogan with the effective contribution of the infrastructure to the performance of teachers in SMA Grobogan 22.8%, while the relative contribution of 29.3%. (4) There is a positive contribution commitment of teachers on teacher performance in SMA Grobogan with the effective contribution of teachers' commitment to the performance of teachers in SMA Grobogan of 31.9%, while the relative contribution of 41.1%